PEMANFAATAN LIMBAH CAIR INDUSTRI PENGOLAHAN TAHU UNTUK MEMPRODUKSI SPORA BACILLUS THURINGIENSIS PENDAHULUAN P SEROVAR ISRAELENSIS DAN APLIKASINYA SEBAGAI BIOKONTROL LARVA NYAMUK - sang gede purnama; Deny SIlvina Pandy; I Gede Sudiana (Program Studi Sarjana Kesehatan Masyarakat Universitas Udayana Berasosiasi Dengan Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI), 2012)
Dengue Hemorrhagic Fever (DHF) in Indonesia, was a public health problem that could not behandled properly until this. This ma! er was proven by always ? nding the number of denguecases continued to increase each year and o en cause death.Based on some study found that the use of the bacterium Bacillus thuringiensis serovar israeliensis(BTI) as bioinsektisida that was proven to be more safe, e? ective and selective in kill mosquitolarvae of Ae. aegypti. Barrier of the use of this bioinsektisida was its price that was expensive,because of being produced by synthesis media. Therefore, researchers was interested to be able to produce Bti with soybean liquid waste knew that during this o en coused water pollution. It isexpected produced BTI with a relatively cheaper price compare than produced by BTI synthesismedia.To be able to prove the liquid soybean waste could be used as a medium BTI than conductedtrials with Bti 4Q1 inoculated in wastewater soybean and Nutrient Broth (synthetic media), andthen compare the number of spores produced from both media. This study was conducted in theBioscience and Biotechnology laboratory, Udayana University, for two months.The results of this study show the liquid soybean waste proved to be able to produce sporesin greater numbers than NB. Apart from the pathogenicity test conducted BTI obtained resultsthat was produced by the liquid soybean waste to have the power to kill a higher than NB. Theadvantages of this study include: media materials was cheap, reduce water pollution, and easyto get it.